Pengaruh Cara Belajar Dan Disiplin Belajar Terhadap Hasil Belajar Mata Pelajaran Mengelola Peralatan Kantor Kelas X Administrasi Perkantoran SMK Batik 1 Surakarta Tahun Pelajaran 2015/2016 - Hera Dwi Suryandari; Djoko Santosa; Tri Murwaningsih (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2017)
The purposes of this research was to determine: (1) presence or absence of a positife and significant effect between how to learn on the learning result of office equipment managements. (2) presence or absence of a positife and significant effect between discipline of learning the learning result of office equipment managements. (3) presence or absence of a positife and significant effect between learning style and discipline of learning on the learning result of office equipment managements. The type of research is clausal correlation methods in quantitative research. The population of this research was all students in grade X office administration skill competency of SMK Batik 1 Surakarta in the academic year of 2015/2016 some 120 students with a sample of 55 students. The sampling technique using proportional random sampling technique. Data callection techniques used were questionnaires and documentation technique. Analysis using the statistical test of multiple regression analysis. Based on the results of data analysis can be summarized as follows: (1) there is a poaitif and significant effect of how to learn on the learning result of office equipment managements, with tobtained > ttabel (3,403 > 2,006), while relative and effective contribution (X1) to (Y) of 49,18% and 50,8%. (2) there is a positif and significant effect of learning discipline on the learning result of office equipment, with tobtained > ttabel (3,595 > 2,006), while relative and effective contribution (X2) to (Y) of 21,59% and 22,3%. (3) there is a positife and significant effect of learning style and learning discipline on the learning result of office equipment managements, with Fobtained > Ftabel (20,379 > 3,17), with R Square percentage of 43,9%.